PAMPERIS POAOENEIS HEIMLICH (LEP., SATYRIDAE) OBSERVACIONES CRITICAS Y RECTIFICACIONES DE LA VENACION ALAR Y GENITALIA DE ESTA ESPECIE - Herrera G., José (Acta Entomológica Chilena, 2022)
A detailed redescription of Pamperis poaoeneis Heimlich (Lep., Satyridae) based on a male topotype in the collection of the Institute, and a critical analysis of the original description of the species is offered in this paper, together with figures of the male wing venation and genital structures.